Parrots have evolved a primate-like telencephalic-midbrain-cerebellar circuit - Gutiérrez-Ibáñez, Cristián; Iwaniuk, Andrew N.; Wylie, Douglas R. (Scientific reports, 2018)
It is widely accepted that parrots show remarkable cognitive abilities. In mammals, the evolution of complex cognitive abilities is associated with increases in the size of the telencephalon and cerebellum as well as the pontine nuclei, which connect these two regions. Parrots have relatively large telencephalons that rival those of primates, but whether there are also evolutionary changes in their telencephalon-cerebellar relay nuclei is unknown. Like mammals, birds have two brainstem pontine nuclei that project to the cerebellum and receive projections from the telencephalon. Unlike mammals, birds also have a pretectal nucleus that connects the telencephalon with the cerebellum: the medial spiriform nucleus (SpM). We found that SpM, but not the pontine nuclei, is greatly enlarged in parrots and its relative size significantly correlated with the relative size of the telencephalon across all birds. This suggests that the telencephalon-SpM-cerebellar pathway of birds may play an analogous role to cortico-ponto-cerebellar pathways of mammals in controlling fine motor skills and complex cognitive processes. We conclude that SpM is key to understanding the role of telencephalon-cerebellar pathways in the evolution of complex cognitive abilities in birds.